2022
DOI: 10.3389/fcell.2022.811075
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Glycosylation Regulators Define Tumor Microenvironment and Immunotherapy in Gastric Cancer

Abstract: Glycosylation (Glyc) is prevalently related to gastric cancer (GC) pathophysiology. However, studies on the relationship between glycosylation regulators and tumor microenvironment (TME) and immunotherapy of GC remain scarce. We extracted expression data of 1,956 patients with GC from eight cohorts and systematically characterized the glycosylation patterns of six marker genes into phenotype clusters using the unsupervised clustering method. Next, we constructed a Glyc. score to quantify the glycosylation inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The consensus clustering algorithm, an unsupervised clustering method, is commonly used for the interpretation of high-dimensional and large datasets. [25][26][27] By performing consensus clustering analysis, Zhang et al 25 DEG analysis is a commonly used approach for identifying genes whose expression is significantly different between two phenotypes. [25][26][27] In the present study, we found that multiple KEGG pathways were significantly different between the two glycosylation pattern groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The consensus clustering algorithm, an unsupervised clustering method, is commonly used for the interpretation of high-dimensional and large datasets. [25][26][27] By performing consensus clustering analysis, Zhang et al 25 DEG analysis is a commonly used approach for identifying genes whose expression is significantly different between two phenotypes. [25][26][27] In the present study, we found that multiple KEGG pathways were significantly different between the two glycosylation pattern groups.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] By performing consensus clustering analysis, Zhang et al 25 DEG analysis is a commonly used approach for identifying genes whose expression is significantly different between two phenotypes. [25][26][27] In the present study, we found that multiple KEGG pathways were significantly different between the two glycosylation pattern groups. To further explore the molecular mechanism underlying how the glycosylation pattern influences the prognosis of PCa, we screened the phenotype-related DEGs between the two glycosylation pattern groups and performed DEG analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations